Yeast and Filamentous Fungi Microbial Communities in Organic Red Grape Juice: Effect of Vintage, Maturity Stage, SO2, and Bioprotection - Windholtz, Sara; Vinsonneau, Emmanuel; Farris, Laura; Thibon, Cécile; Masneuf-Pomarède, Isabelle (Frontiers in Microbiology, 2021)
Changes are currently being made to winemaking processes to reduce chemical inputs (particularly sulfur dioxide (SO2)) and adapt to consumer demand. In this study, yeast growth and fungal diversity were investigated in merlot during the prefermentary stages of a winemaking process without addition of SO2. Different factors were considered, in a two-year study: vintage, maturity level and bioprotection by the adding yeast as an alternative to SO2. The population of the target species was monitored by quantitative-PCR, and yeast and filamentous fungi diversity was determined by 18S rDNA metabarcoding. A gradual decrease of the α-diversity during the maceration process was highlighted. Maturity level played a significant role in yeast and fungal abundance, which was lower at advanced maturity, while vintage had a strong impact on Hanseniaspora spp. population level and abundance. The presence of SO2 altered the abundance of yeast and filamentous fungi, but not their nature. The absence of sulfiting led to an unexpected reduction in diversity compared to the presence of SO2, which might result from the occupation of the niche by certain dominant species, namely Hanseniaspora spp. Inoculation of the grape juice with non-Saccharomyces yeast resulted in a decrease in the abundance of filamentous fungi generally associated with a decline in grape must quality. Lower abundance and niche occupation by bioprotection agents were observed at the overripened stage, thus suggesting that doses applied should be reconsidered at advanced maturity. Our study confirmed the bioprotective role of Metschnikowia pulcherrima and Torulaspora delbrueckii in a context of vinification without sulfites.